Effect of silicification on the tableting performance of cellulose II: A novel multifunctional excipient (2021)
ABSTRACT: The effect of silicification on the tableting performance of microcrystalline cellulose II (MCCII) was assessed through coprocessing with fumed silica via spray drying and wet granulation at the 98: 2, 95: 5, 90: 10 and 80:20 ratios. Compacts produced by spray drying and wet granulation rendered better tensile strength than MCCII. The Kawakita and Heckel models implied that silicification increased compressibility and decreased the plastic deforming behavior and densification by die filling at the early stage of compression for MCCII. It also decreased the sensitivity to hydrophobic lubricants such as magnesium stearate, especially for the spray-dried products due to the competing effect with magnesium stearate. Further, silicification decreased the high elastic recovery typical of MCCII due to the increase in specific surface area and fragmenting behavior which contributed to the formation of stronger compacts. Moreover, silicification did not affect the fast disintegrating properties and release rates of poorly soluble drugs such as griseofulvin formulated in tablets compared to those of Prosolv® SMCC 50 and Prosolv® SMCC 90. The new silicified materials are appropriate to formulate fast disintegrating tablets by direct compression.